1999
DOI: 10.1111/j.1600-0714.1999.tb01997.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in collagen and fibronectin phagocytosis by human buccal mucosa fibroblasts in vitro as a possible mechanism for oral submucous fibrosis

Abstract: Oral submucous fibrosis (OSF), a chronic oral mucosal condition commonly found in south Asians, is a disorder characterized by a quantitative as well as a qualitative alteration of collagen deposition within the subepithelial layer of the oral mucosa. Since degradation of collagen by fibroblast phagocytosis is an important pathway for physiological remodelling of soft connective tissues, we have investigated phagocytosis of collagen‐ and fibronectin‐coated latex beads by fibroblast cultures with an in vitro mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…As OSF shows a gross imbalance in ECM remodeling, this putative mechanism was investigated in vitro [29]. A decrease of the phagocytic activity of fibroblasts in OSF patients when compared with the normal persons has been earlier reported [31]. The number of phagocytic cells and phagocytic activity in cultured human oral fibroblasts from OSF site was lower than the fibroblasts from the normal regions of the same person.…”
Section: Discussionmentioning
confidence: 92%
“…As OSF shows a gross imbalance in ECM remodeling, this putative mechanism was investigated in vitro [29]. A decrease of the phagocytic activity of fibroblasts in OSF patients when compared with the normal persons has been earlier reported [31]. The number of phagocytic cells and phagocytic activity in cultured human oral fibroblasts from OSF site was lower than the fibroblasts from the normal regions of the same person.…”
Section: Discussionmentioning
confidence: 92%
“…It affects the mucosa of any part of oral cavity and occasionally extending into the pharynx and esophagus. (1,2) The pathogenesis of the disease is not well established. Since its first description various etiopathological concepts have been put forward such as spices (chilies), nutritional deficiencies, genetic susceptibility, lysyl oxidase, autoimmunity and one of the most accepted is areca nut usage.…”
Section: Introductionmentioning
confidence: 99%
“…In the areca nut chewers the Lysl oxidize activity is unregulated to alter fibroblast metabolism producing more collagen. This may add to the conclusion of the occurrence of OSF due to the products leaching out from areca nut causes OSF and not from those leaching out from tobacco [1,27].…”
Section: Discussionmentioning
confidence: 90%
“…The occurrence of OSF was seen significantly in those having one or the other forms of areca nut which showed that the product which leaches out from areca nut would be responsible for the development of OSF [1,27]. People having tobacco alone have never been seen to have OSF.…”
Section: Discussionmentioning
confidence: 99%